Studi Efektivitas Pembelajaran Terpadu Ilmu Pengetahuan Sosial di Sekolah Menengah Pertama - Heni Waluyo Siswanto (Jurnal Pendidikan dan Kebudayaan, 2011)
The aim of this study is to collect information regarding to: 1) the description of teachers ability to implement the competency of Integrated Learning of Social Sciences (IPS); 2) the view that each teacher has a different background of science discipline of integrated learning; and 3) the ability of teachers in implementing effective integrated learning based on â€œteam teachingâ€. Research conducted in 3 provinces assigned by purposively random, namely: Semarang, Medan, and Makassar. The result of the study shows a clear and significant result, that is the integrated learning social science in junior high school, both good category or medium category does not take place effectively. Some of the obstacles that led to the ineffectiveness of these are as follows: 1) the discrepancy ability of social studies teacher in junior high school is high enough to describe the competence of social science subjects due to their educational background of science discipline; 2) there is no clear meaning of mission from point of view of social science integrated learning teachers of junior high school who have different disciplines of science background, so that the integrated learning carried out only based on each individual perspectives and capabilities; 3) the implementation of social science integrated learning in junior high school can not be done optimally, because the allocation is constrained by the limitations of time and lessons schedule that are not designed and/or arranged for the benefit of an integrated learning approach based on â€œteam teachingâ€.Â ABSTRAKÂ Studi ini bertujuan untuk menggali informasi mengenai:1) kemampuan guru menjabarkan kompetensi IPS untuk melaksanakan pembelajaran terpadu; 2) pandangan guru yang masing-masing memiliki perbedaan latar belakang cabang keilmuan mengenai pembelajaran terpadu; dan 3) kemampuan guru melaksanakan pembelajaran terpadu yang efektif berbasis pada â€œteam teachingâ€. Penelitian diselenggarakan di 3 provinsi yang ditetapkan secara random purposif, yaitu: Semarang, Medan, dan Makassar. Hasil penelitian menunjukkan bahwa pembelajaran terpadu IPS di SMP, baik kategori baik maupun kategori sedang, tidak berlangsung secara efektif. Beberapa kendala yang menyebabkan ketidakefektifan yaitu: 1) kompetensi mata pelajaran IPS yang disebabkan oleh latar belakang pendidikan mereka yang berbasis cabang keilmuan; 2) pemaknaan yang tidak jelas terhadap misi pembelajaran terpadu IPS tampak dari pandangan guru IPS di SMP yang masing-masing memiliki perbedaan latar belakang cabang keilmuan, sehingga pembelajaran terpadu dilaksanakan hanya berdasarkan pada perspektif dan kemampuan individual masing-masing; dan 3) pelaksanaan pembelajaran terpadu IPS di SMP tidak bisa dilakukan secara optimal, karena terkendala keterbatasan alokasi waktu dan jadwal pelajaran yang tidak dirancang dan/atau disusun untuk kepentingan pembelajaran terpadu yang berbasis pada pendekatan â€œteam teachingâ€.